Kisah Kelabu di Balik Maraknya Pers Lokal Di Kalimantan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Drwan upon three filters of political econmic analysis of mass media, namely concentrated ownership, advertising and the dynamism of audience, this article uncover a local press in Kalimantan.For the sake gaining maximal profit they fail to perform as watch dog and safeguarding moral idealism Kata-kata kunci:media lokal, monopoli media, iklan khalayak